Incorporating Ecohydrological Processes Into an Analysis of Charcoal-Livestock Production Systems in the Tropics: An Alternative Interpretation of the Water-Energy-Food Nexus - Mwampamba, Tuyeni H.; van Schaik, N. Loes M. B.; Castillo Hernandez, Luis A. (Frontiers in Environmental Science, 2018)
In the tropics, livestock grazing usually occurs simultaneously with charcoal production, yet empirical understanding of the combined activities remains poor, especially as regards to their effects on hydrological functions. Given predicted growth in both charcoal and beef production in Sub-Sahara Africa, South East Asia, and Central and South America, understanding the potential effects of maintaining this dual production system on local and landscape level hydrological dynamics is paramount for ensuring long-term ecosystem sustainability. Based on a synthesis of existing literature, we propose a theoretical and conceptual framework for analyzing the interlinks between charcoal, livestock, and hydrological processes where they co-exist. In a silo approach, we analyze the isolated effects of charcoal production and livestock on hydrological processes before exploring their combined effects (systemic approach). Given the scarcity of studies that explicitly treat the influence of traditional small-scale charcoal production on hydrological processes, we base our findings on existing knowledge about deforestation, forest fire and grazing impacts on hydrology. We find that exclusion of the effects of companion activities and omission of information on the intensity of biomass harvesting (i.e., pruning branches, selective harvest, clear cutting, uprooting tree stumps) can lead to over-attributing changes in hydrological processes to charcoal, thus exaggerating the effects on vegetation which might lead to inappropriate interventions. We also find that, in the case of livestock keeping, impacts on hydrological processes are highly dependent on grazing intensity, with low intensity grazing possibly having negligible or even positive effects on forest regrowth and thereby restoration of hydrological processes. Thus, the charcoal-livestock-water nexus may have a wide range of outcomes for hydrological processes ranging from negligible to highly profound effects, depending on key decisions in management and practice. To test these finding, however, field studies are needed with an explicit focus on the combined effects of different biomass harvesting practices and grazing intensities on hydrological processes across different scales. Albeit conceptual at this stage, we believe that our approach is a necessary first step in the process of diagnosing potential shortcomings of past approaches for studying charcoal production systems and developing new understanding of this three-way nexus.